Faktor Yang Mempengaruhi Minat Masyarakat Membayar ZIS (Studi di Baitul Mal Sigli) - Desiana, Rina; Amri, Khairul; Maulida Yani, Nanda (Jeksyah: Islamic Economics Journal, 2022)
Zakat, Infaq, and Alms (ZIS) is one of the worships in Islam to seek the pleasure of Allah SWT. To optimally empower Zakat, Infaq, and Alms funds, a professional, trustworthy and transparent management institution is needed. This study was conducted to determine the factors that influence people's interest in paying ZIS through Baitul Mal Sigli, Pidie Regency. This research is a field research using quantitative analysis methods. Sampling method using Non-Probability Sampling with Incidental Sampling technique. The sample used in this study were 50 people. The data used in this study is primary data which is data obtained directly from respondents by distributing questionnaires. The results of the multiple regression analysis show that the religiosity factor has a positive and significant effect on people's interest in paying ZIS through Baitul Mal Sigli, Pidie Regency, on the other hand, trust and religiosity factors have no significant effect on people's interest in paying ZIS through Baitul Mal Sigli, Pidie Regency.